Hexamerization and thermostability emerged very early during geranylgeranylglyceryl phosphate synthase evolution. (11th January 2021) - Kropp, Cosimo; Straub, Kristina; Linde, Mona; Babinger, Patrick
Abstract: A large number of archaea live in hyperthermophilic environments. In consequence, their proteins need to adopt to these harsh conditions, including the enzymes that catalyze the synthesis of their membrane ether lipids. The enzyme that catalyzes the formation of the first ether bond in these lipids, geranylgeranylglyceryl phosphate synthase (GGGPS), exists as a hexamer in many hyperthermophilic archaea, and a recent study suggested that hexamerization serves for a fine‐tuning of the flexibility – stability trade‐off under hyperthermophilic conditions. We have recently reconstructed the sequences of ancestral group II GGGPS enzymes and now present a detailed biochemical characterization of nine of these predecessors, which allowed us to trace back the evolution of hexameric GGGPS and to draw conclusions about the properties of extant GGGPS branches that were not accessible to experiments up to now. Almost all ancestral GGGPS proteins formed hexamers, which demonstrates that hexamerization is even more widespread among the GGGPS family than previously assumed. Furthermore, all experimentally studied ancestral proteins showed high thermostability. Our results indicate that the hexameric oligomerization state and thermostability were present very early during the evolution of group II GGGPS, while the fine tuning of the flexibility – stability trade‐off developed very late, independent of the emergence of hexamerization.